(untitled) (Eurasian Journal of Learning and Academic Teaching, 2024)
As our population ages, maintaining cognitive function and mental well-being in older adults becomes increasingly important. While traditional methods of cognitive stimulation, such as puzzles and memory exercises, have long been advocated, emerging research suggests that an unconventional activity—gaming—may hold significant promise in this regard. In this article, we delve into the cognitive benefits of gaming for older adults, exploring how gaming can help maintain cognitive function, improve memory, problem-solving skills, and hand-eye coordination